Search And Isolation of Endophytic Bacteria from Medicinal Plants and Determination of Their Morphological and Cultural Properties. - Shokhiddinova Mokhichekhra; Tojiyeva Maftuna; Tojiyev Bekhruz (Genius Journals, 2021)
7 isolates were isolated from the roots, stems and leaves of the medicinal plant Kalanchoe degremona. MALDI TOF (MALDI TOF) was identified using mass spectrometry and in Pseudomonas puti, Bacillus amyloliquefaciens ssp. Plantarum was found to belong to the species Klebsiella pneumoniae, Bacillus subtilis.
Keywords: Endophytes; bacteria; Melissa officinalis; medicinal plants